STA Boost: an innovative digital solution to enhance student engagement in introduction to statistics - Muhammad Nur Ismail, Mohamad Nurshahnazim; Abdul Halil, Muhammad Lutfil Hadi; Wong, Geoffery Marvin; Mohamad Ashree, Mohamad Iqmall Hakimi; Badarul Azam, Akmal Shafiq (2025)
STA Boost is a digital learning tool designed to enhance student engagement and understanding in the Introduction to Statistics course. Designed using a no-code platform, the app provides structured, topic-based notes and a range of interactive learning games that support both classroom use and self-directed study. This innovation addresses common challenges in statistics education, such as difficulty in understanding abstract concepts, low motivation, and limited access to engaging learning materials. Selected topics from the syllabus are presented in a simplified format, accompanied by interactive single-player and multiplayer games that reinforce learning through quizzes, puzzles, and timed challenges. These features help students actively recall and apply statistical concepts in a fun and meaningful way. STA Boost is accessible on multiple devices through a simple shareable link, with no installation required. It was developed entirely using free digital tools, making it a cost-effective and scalable solution for educational institutions. Feedback from 67 students revealed highly positive responses, with common descriptors including "enjoyable," "educational," and "interactive," indicating strong engagement and satisfaction. By promoting digital literacy, active learning, and flexible access, STA Boost aligns with the goals of 21st-century education. It provides a practical solution to enhance the teaching and learning of introductory statistics